Implikasi Pendidikan Karakter Peserta Didik dalam Q.S Al Hujurat Ayat 1-5 Menurut Tafsir Ibnu Katsir - Pratama, Andy Riski (al-Urwatul Wutsqo : Jurnal Ilmu Keislaman dan Pendidikan, 2023)
Morals that hit some students in the country. One indicator of the crisis is due to the widespread coverage in the mass media related to impolite behavior by students in a number of educational institutions in the country, this issue shows that the practice of moral attitudes for students is very important in Islamic education. Therefore students must have good attitudes or morals towards educators, with a good attitude possessed by students and educators it is hoped that the goals of Islamic education can be achieved properly. As for the focus of the problem in this study is how the interaction of students with educators in Q.S al-Hujurat verses 1-5 and its realization in Islamic education. The approach used in this research is library research (literature study), namely deepening, studying and identifying existing knowledge in the literature (reference books or other research results) related to the discussion under study. In this discussion, the method used is the deductive method. From the results that the author shows, it shows that the morals of students and educators have a polite attitude as contained in the contents of Al-Hujurat verses 1-5, that is, students may not imitate while walking with educators, unless they ask permission, when we are Talking with educators, we are not justified in speaking loudly like talking to our neighbors, but in a voice that is soft and full of fear. The implication in Islamic education, the attitude that students should have in interacting with educators is to imitate what has been explained by Allah in Q.S al-Hujurat verses 1-5, so with this all the rules regarding politeness will be applied in Islamic education.